PENGEMBANGAN INSTRUMEN PENILAIAN PSIKOMOTOR PADA MATERI SISTEM PENCERNAAN KELAS XI SMA - Maharani, Ade Dewi; Aima, Zulfitri (STKIP PGRI Sumatera Barat, 2014)
The result of supervision and evaluation of KTSP 2009 finds some things that become difficulties for teachers in managing the psychomotor assessment tools. Difficulties referred to, among others, how to determine the operational verb in accordance with the level of competence in psychomotor, techniques to develop indicators of achievement in the field of psychomotor, assessment tools and strategies to prepare the appropriate exam materials related to characteristics of psychomotor aspects and how to carry out an objective assessment, so that the necessary development of assessment instruments psychomotor valid and practical in the material of digestive system. This research is a development (research for the development) that uses model Fenrich, namely analysis (analysis), planning (planning), design (design), development (development), implementation evalution (implementation), evalution (evaluation) and revision (revision) Implementationdan evalution phase was not conducted. Validation of data was obtained from the validation sheet filled out by experts and practical that were obtained from a questionnaire completed by the practitioner. Validity measured includes material aspects, aspects of instrument construction, and aspects of the language. The practicalities of measuring the ease of designing and using assessment instruments psychomotor developed. Data were analyzed with descriptive analysis in the form persentage.Instrument of psychomotor assessment on the material digestive system is designed in the form of performance assessment, products, projects which are completed with assessment rubrics of each instrument. The tests of psychomotor assessment instruments are categorized as very valid with an average value for the performance appraisal instrument (performance) i.e. 90.3%, 92.2% is product assessment instruments, and project assesment insrument i.e.97.4%. While the level of psychomotor assessment instruments is categorized practicality with an average value i.e 72.23%.